Nutrient Utilisation and Performance of Murrah Buffalo Calves Fed Palm Press Fibre and Sheanut Cake (Vitellaria paradoxa) Based Complete Diets - Kumar, M. Kishan (Indian Journal of Animal Nutrition, 2017)
Two complete diets (roughage, concentrate ratio, 40: 60) in mash form (R II and R III) were formulated using palm press fibre (20 and 15%) and chopped jowar strover (20 and 25%) as roughage source and sheanut cake (18.5 and 28%) along with locally available concentrate ingredients and compared with conventional ration (R I) (consisting of chopped jowar stover, chopped jowar fodder and concentrate mixture, fed separately) for growth performance, nutrient digestibility and cost economics in graded Murrah buffalo calves for aduration of 180 days. The digestibility of DM, OM, CP, EE, and NFE was higher (P